2023
DOI: 10.3390/su15043475
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Whole Milk Powder Production by a Cumulative Exergy Consumption Approach

Abstract: The production of food is a sector that consumes a significant amount of energy and encompasses both agricultural and industrial processes. In this study, the energy consumption of whole milk powder production, which is known to be particularly energy-intensive, was examined. The study used a cumulative exergy consumption approach to evaluate the overall production process of whole milk powder, including the dairy farm (raw milk production) and dairy factory (powder production) stages. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…This shows the importance of focusing on energy efficiency and de- The analysis of this process has drawn a lot of research to improve historical procedures [34][35][36] in which all steps and energy provided were considered individually. Uçal et al [37] analyzed a whole milk powder (WMP) production line principally based on natural gas for heating purposes and showed that pasteurization, evaporation, and drying represented 98.3% of the energy consumption and 95.7% of the CO 2 emissions-for a total of 10.2 MJ/kg WMP and 0.588 kg CO2 /kg WMP . Similar results are found in Ramirez et al with 11.1 MJ/kg WMP [32].…”
Section: Dairy Application: Sterilized Milk Powdermentioning
confidence: 99%
“…This shows the importance of focusing on energy efficiency and de- The analysis of this process has drawn a lot of research to improve historical procedures [34][35][36] in which all steps and energy provided were considered individually. Uçal et al [37] analyzed a whole milk powder (WMP) production line principally based on natural gas for heating purposes and showed that pasteurization, evaporation, and drying represented 98.3% of the energy consumption and 95.7% of the CO 2 emissions-for a total of 10.2 MJ/kg WMP and 0.588 kg CO2 /kg WMP . Similar results are found in Ramirez et al with 11.1 MJ/kg WMP [32].…”
Section: Dairy Application: Sterilized Milk Powdermentioning
confidence: 99%
“…However, with more advanced power electronics, there will be more smart terminals with metering capabilities and, therefore, the amount of data generated will far exceed what was originally to be processed [62]. This requires that these measurement devices themselves have greater processing and transmission capabilities and can share the workload for the data processing centers [63]. For example, when there are smart terminals, such as electric vehicle setups, more detailed information such as load detection can be obtained using sensors.…”
Section: Intelligent Electrical Terminalsmentioning
confidence: 99%